Hollywood y la Guerra Civil española: análisis de sus tres únicas cintas de ficción coetáneas (1937-1938) = Hollywood and the Spanish Civil War: analysis of its only three fiction films made simultaneously (1937-1938) (Estudios Humanísticos. Filología, 2017)
El presente artículo propone un análisis comparativo de las tres únicas películas realizadas por Hollywood sobre la Guerra Civil española mientras esta se desarrollaba: The Last Train From Madrid (James Hogan, 1937), Love Under Fire (George Marshall, 1937) y Blockade (William Dieterle, 1938). A la postre, se demostrará que, en contra de lo afirmado por buena parte de la historiografía, las tres –y no únicamente Blockade– efectúan una denuncia de la intervención de las potencias del Eje en la Guerra Civil española.The purpose of this article is to provide a comparative analysis of the only three films that were made in Hollywood relating to the Spanish Civil War during the period in which it was being waged: The Last Train From Madrid (James Hogan, 1937), Love Under Fire (George Marshall, 1937) and Blockade (William Dieterle, 1938). Lastly, it will be demonstrated that, contrary to what has been asserted by a large num- ber of historians, all three – not only Blockade – express criticism against the Axis powers’ intervention in the Spanish Civil War.